Journal of the Academy of Marketing Science (JAMS) - Jarvis, W.; Pettigrew, Simone; Olaru, D. (Academy of Marketing Science, Springer, 2013)
It has been shown that heterogeneity in worded alcohol warning statement effectiveness affects young people’s choice behaviour. This heterogeneity has been found to be closely aligned to gender differences. In this study, the research is extended by considering the influence of alcohol category (type) on choice and how this preference influences warning statement effectiveness. Choice tasks combining different branded alcohol types, alcohol content and warning statements were presented online as labels. The context was 18-25 year old drinkers in Australia. The results showed that while gender is a significant covariate for the different latent classes in the data, it doesn’t improve overall model fit. Alcohol category preferences drive choice behaviour and differences exist with regards to how warning statements are processed. With certain pre-mixed beverages and wine, worded statements in larger font size had significant negative impact on choice. With rum drinkers, simpler cues of size and the use of the word “WARNING” in front of the statement had a negative impact on choice. With beer drinkers, neither statement nor orientation of the statement influenced choice. The results suggest new warning statements strategies for dealing with heterogeneity in the wider alcohol market.